Encyclopedia of Language and Education
XVII, 272 p.
Keywords: In many parts of the world, it is common for a child to grow up speaking a local language at home, another in the market place, adding another to her repertoire as a lingua franca, and then adding a language of wider communication such as English or French if she continues her formal schooling. The contributions to the volume examine in some detail diverse aspects of second language education, ranging from a focus on the basic contributions of linguistic theory and research to our understanding of second language learning and teaching on the one hand, to a series of reviews of innovative language education practices in selected regions of the world on the other. For the purposes of this volume, second language education has been defined operationally to encompass education which occurs in those settings and situations in which a dominant language is offered as a second language (e.g., ESL in England or the United States whether as a subject of study or a vehicle through which other material is studied), as well as those cases in which an official, but not necessarily dominant, language is mandated (e.g., French or English in certain parts of the Middle East or the Mahgreb). The contributions also focus mainly, albeit not exclusively, on second language education for school-aged learners.